Natural-born cyborgs - Clark, Andy (Oxford University Press, 2003)
Machine generated contents note: Introduction --CHAPTER 1 Cyborgs Unplugged --CHAPTER 2 Technologies to Bond With --CHAPTER 3 Plastic Brains, Hybrid Minds --CHAPTER 4 Where Are We? --CHAPTER 5 What Are We? --CHAPTER 6 Global Swarming --CHAPTER 7 Bad Borgs? --CHAPTER 8 Conclusions: Post-Human, Moi? --Notes --Index